Implementing primary care concepts in higher education: a mixed method study in Flanders (Belgium) - Lotte Vanneste; Sam Pless; Sandra Martin; Emily Verté; Roy Remmen; Pauline Boeckxstaens; Peter Pype; Reini Haverals; Dagje Boeykens; Dominique Van de Velde; Patricia De Vriendt; on behalf of the Primary Care Academy (BMC Primary Care)
Abstract Background The policy shift towards person-centred integrated primary care systems drives interest in primary care across higher education programs. In Flanders, the Primary Care Academy (PCA) is established to support this policy shift. The PCA focusses on the concepts of goal-oriented care, self-management, and interprofessional collaboration to support the shift towards integrated care and to integrate them in curricula in order to strengthen and develop a futureproof health system. Therefore, the aim of this study is if and how lecturers implement these concepts in the curriculum and what they need for a successful implementation. Methods A sequential explanatory mixed method study design was used combining quantitative and qualitative data. A cross-sectional survey was sent to 276 Flemish health care education programs. Qualitative data was collected through focus groups in which lecturers participated. Results The results showed that 89% of the higher education programs address goal-oriented care, self-management, and interprofessional collaboration with regard to primary care. Further analysis of courses within the programs reveals that the concept of self-management is covered in only 58%, while goal-oriented care (73%) and interprofessional collaboration (80%) appear more frequently. The level at which the themes are addressed in the courses are often limited to an introduction. The focus groups revealed that primary care is present in education programs, however lecturers are limited aware where primary care is integrated in their own and other programs. Lectures expressed a need for more collaboration between research, education and practice in developing educational content. When new concepts are introduced, lecturers want them to be translated into educational content, learning objectives and competencies. Conclusions The study shows that the concepts of goal-oriented care, self-management, and interprofessional collaboration are present in higher education programs to a varying degree. Lecturers are eager to implement these new primary concepts but they lack collaboration between education, research and practice. Lecturers indicate the need for a competence profile for primary care professionals as common framework to guide curriculum development.